HUBUNGAN KADAR TIMBAL (Pb) DALAM DARAH DENGAN INSOMNIA PADA REMAJA JALANAN DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - , IDA KURNIAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ida Kurniawati*, Sri Sutarni S**, Cempaka Thursina S** *Student of Faculty of Medicine Gadjah Mada University **Senior Staff of Neurology Department RSUP Dr. Sardjito Background: Insomnia is the commonest sleep complaint in population. About 30-40% adults have insomnia. Insomnia disturbs daily activity and reduces quality of life. Insomnia is an early symptom of lead toxicity due to acute and chronic exposure. Pathophysiology of lead induced insomnia is unknown. It is estimated that lead induced insomnia involves neurotransmitters disturbance and imbalance, for example disturbance of GABA neurotransmitter. Objective: The aim of this study was to determine association between blood lead level and insomnia in street adolescents in Daerah Istimewa Yogyakarta (DIY). Subject and Method: The subjects were 55 street adolescents in DIY from rumah singgah Girlan Nusantara, Prambanan. This study used analytic observational method with cross-sectional design. Result: Subjects who had insomnia were 3 people (15,0%) in blood lead level â¥ 10 Î¼g/dL and 17 people (85,0%) in blood lead level < 10 Î¼g/dL. Bi-variant analysis showed a significant association between blood lead level and insomnia with p=0,021 and RP=0,210 (95% CI=0,052- 0,846). Another variable did not have significant association with insomnia (p>0,05). Conclusion: Blood lead level did not have significant association with insomnia in street adolescents in Daerah Istimewa Yogyakarta (DIY).